(untitled) (Actual Problems of Psychology in Educational Institutions, 2018)
The article envisages the efficiency of implementation of training program aiming at the prevention negative mental states. It is noted that mental states are very important in the life of modern primary school age сhildren. The focused on the fact that a trainings are very different. The results of the research are analyzed and the structure and level of negative mental states at students of primary school age. The analyzed training as a way of prevention of negative mental states at students of primary school age.